Pylon-Climber: a novel climbing assistive robot for pylon maintenance. Issue 1 (16th January 2017) - Lu, Xiaolong; Zhao, Shiping; Yu, Deping; Liu, Xiaoyu
Abstract : Purpose: The purpose of this paper is to describe the design and development of "Pylon-Climber", a pole climbing robot (PCR) for climbing along the corner columns of electricity pylon and assisting the electricians to complete maintenance tasks. Design/methodology/approach: Introduces a PCR that is composed of a simple climbing mechanism and two novel grippers. The gripper consists of two angle-fixed V-blocks, and the size of V-block is variable. The clamping method of the angle bar meets the requirement of the force closure theorem. The whole design adopts symmetrical design ideas. Findings: The developed prototype proved possibility of application of PCRs for inspection and maintenance of pylon. The novel gripper can provide enough adhesion force for climbing robot. Practical implications: The robot is successfully tested on a test tower composed of different specification steel angles, oblique ledges and overlapping steel struts. Originality/value: Design and development of a novel climbing assistive robot for pylon maintenance. The robot is able to climb along the column of electricity pylon and pass all obstacles. The gripper can reliably grasp the angle bar with different specification and overlapping steel struts from multiple directions.